Identifying Barriers to Financing Knowledge-Based Businesses with Emphasis on the Role of the Banking System - Farahbakhsh, Reza; Raeispour Rajabali , Ali; Zayandehroodi, Mohsen (Business, Marketing, and Finance Open, 2024)
This study aims to identify the barriers to financing knowledge-based businesses, with an emphasis on the role of the banking system. The research method is qualitative and grounded theory-based. The statistical population consists of all banks that provided credit and facilities to knowledge-based companies, including the following banks: Shahr Bank, Bank Melli, Bank Mellat, Bank Resalat, Bank Saderat, Bank of Industry and Mine, and Export Development Bank of Iran. Sampling was conducted purposively and non-randomly. The research instrument was semi-structured interviews conducted with 15 experts and specialists in financing knowledge-based businesses. In addition, document analysis was used to identify dimensions, characteristics, facilitating and inhibiting factors, and appropriate methods for financing knowledge-based businesses. To ensure validity and reliability, the Lincoln and Guba evaluation method was applied. The interviews were reviewed multiple times, and initial concepts were extracted through content analysis. Based on the conducted analyses, the identified barriers to financing knowledge-based businesses, emphasizing the role of the banking system, include causal conditions such as factors influencing financing knowledge-based businesses (laws and regulations, structure and organization, monitoring and evaluation), contextual conditions such as supportive programs, the central phenomenon of collaboration, intervening conditions such as effective management, strategies such as investment, and outcomes including collaboration and networking, attracting investments, market development, increased production capacity, and technological advancement.